2020
DOI: 10.3389/fnbeh.2020.00053
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Hippocampal Volume as a Function of BMI and Reward Sensitivity

Abstract: Sensitivity to reward is a personality trait that predisposes a person to several addictive behaviors, including the presence of different risky behaviors that facilitates uncontrolled eating. However, the multifactorial nature of obesity blurs a direct relationship between the two factors. Here, we studied the brain anatomic correlates of the interaction between reward sensitivity and body mass index (BMI) to investigate whether the coexistence of high BMI and high reward sensitivity structurally alters brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…Thus, it has become clear that the hippocampus actively participates in the decision-making of food consumption by altering the prediction of hedonic consequences of feeding [ 47 ]. Neuroimaging studies have shown that hippocampal volume is diminished with aberrant neural activity in obese individuals compared to lean healthy individuals [ 48 , 49 , 50 ], indicating a potential mechanistic link between hippocampal function and metabolic health. Consistent with these results, rodent studies indicate that diet-induced obesity (via HFD or high-sucrose diet) manifests impaired memory consolidation [ 51 , 52 , 53 ] that is associated with hippocampal BBB disruption [ 54 , 55 ], thereby potentially increasing the entry of systemic inflammatory mediators into the hippocampus.…”
Section: Mitochondrial Dysfunction In the Cnsmentioning
confidence: 99%
“…Thus, it has become clear that the hippocampus actively participates in the decision-making of food consumption by altering the prediction of hedonic consequences of feeding [ 47 ]. Neuroimaging studies have shown that hippocampal volume is diminished with aberrant neural activity in obese individuals compared to lean healthy individuals [ 48 , 49 , 50 ], indicating a potential mechanistic link between hippocampal function and metabolic health. Consistent with these results, rodent studies indicate that diet-induced obesity (via HFD or high-sucrose diet) manifests impaired memory consolidation [ 51 , 52 , 53 ] that is associated with hippocampal BBB disruption [ 54 , 55 ], thereby potentially increasing the entry of systemic inflammatory mediators into the hippocampus.…”
Section: Mitochondrial Dysfunction In the Cnsmentioning
confidence: 99%
“…There was also some evidence of structural and resting state differences in the PFC in relation to BAS trait measures (Adrián-Ventura et al, 2019b;Hahn et al, 2012;Li et al, 2014). The involvement of the VS as a BAS structure was consistently supported by correlations with task-related activity (Costumero, Barro ´s-Loscertales, Bustamante, Ventura-Campos, Fuentes, & Ávila, 2013; Costumero, Barro ´s-Loscertales, Bustamante, Ventura-Campos, Fuentes, Rosell-Negre, et al, 2013;Costumero et al, 2016;Dong et al, 2018;Eryilmaz et al, 2017;Hahn et al, 2009Hahn et al, , 2011Mortensen et al, 2015;Radke et al, 2016;Simon et al, 2010;van Rijn et al, 2016) and structural and resting state differences (Adrián-Ventura et al, 2019b;Barro ´s-Loscertales et al, 2006a;Hahn et al, 2012;Parcet et al, 2020). BAS was also found to be related to connectivity between the right and left striatum and right frontal gyrus and right striatum (Dong et al, 2018).…”
Section: Discussionmentioning
confidence: 89%
“…Of the studies using the SRSPQ, two studies found a positive correlation between sensitivity to One study, using an all-male sample, found a negative correlation with GMV in the caudate, putamen, superior frontal cortex, and globus pallidus (Barro ´s-Loscertales et al, 2006b). Another study also found a negative correlation between SR and GMV in the left caudate (Parcet et al, 2020). The final study that investigated SR found a negative correlation with GMV in the ACC, the medial and left lateral PFC, left and superior temporal lobe and the left insula for both genders, and in the NAcc and left caudate for males only (Adrián-Ventura et al, 2019b).…”
Section: Structural Studies Looking At Gray Matter Volumementioning
confidence: 86%
“…Furthermore, the relationships between SR and SP and brain volume in risky driving contexts have not yet been studied, although some studies have explored the association between brain volume and personality traits such as SP and SR or impulsivity. Regarding SR, positive and negative correlations have been found with the volume of the striatum ([ 25 28 ]) and negative correlations with the volumes of the lateral and medial prefrontal and superior temporal cortices [ 25 , 27 , 29 ]. On the other hand, SP has been positively correlated with volumes of the amygdala and hippocampal formation and negatively with the insula and OFC volumes [ 25 , 30 35 ].…”
Section: Introductionmentioning
confidence: 99%